Adaptive Household Agroforestry Design Strategies For Sustainable Landscape Services In Riparian Settlements Of Tangerang City - Muhammad Rasyidul Ilmi, Muhammad Rasyidul Ilmi; Musyaffa Rifqi Harimardika, Musyaffa Rifqi Harimardika; Achnia Tiffany Nurfadillah, Achnia Tiffany Nurfadillah; Hannisa Handri, Hannisa Handri; Intan Agustina Pratiwi, Intan Agustina Pratiwi (Journal of Synergy Landscape, 2025)
The rapid development of urban settlements along the Cisadane River riparian zone has led to the decline of green open spaces, reducing the landscape services essential for environmental resilience. This study examines the characteristics and management of pekarangan (house yards) in formal and informal settlements to develop adaptive design concepts that enhance ecological and socio-economic landscape services. The research was conducted in three riparian segments—upstream, midstream, and downstream—of Tangerang City, involving 60 pekarangan samples (30 formal and 30 informal). Data were collected through field observations, interviews, and spatial mapping. Analyses included descriptive statistics, the Shannon-Wiener biodiversity index, and qualitative interpretation. Results showed that pekarangan in formal and informal areas share vertical and horizontal plant diversity, dominated by ornamental and food plants, with high biodiversity index values (H' = 3.5–4.3). Informal settlements primarily utilize pekarangan for practical daily functions, while formal settlements emphasize aesthetics. Economic and social conditions influence management practices such as watering, pruning, and composting. The study proposed a pekarangan development model based on zoning principles: social (front), productive (side), and service (rear) zones, combined with multistrata vegetation and biopore infiltration technology. These adaptive design strategies contribute to ecological resilience, urban food security, and cultural sustainability in riparian communities.